New sights into lipid metabolism regulation by low temperature in harvested Torreya grandis nuts. (19th March 2019) - Zhou, Minying; Song, Lili; Ye, Shan; Zeng, Wei; Hännien, Heikki; Yu, Weiwu; Suo, Jinwei; Hu, Yuanyuan; Wu, Jiasheng
Abstract: BACKGROUND: Torreya grandis, a large evergreen coniferous tree with oil‐rich nuts, undergoes a crucial ripening stage after harvest that results in oil accumulation, finally giving rise to the nut that is edible in roasted form. To understand lipid metabolism in T. grandis nuts during the post‐harvest ripening period, the effects of low temperature on lipid content, fatty acid composition, lipid biosynthesis and degradation were investigated. RESULTS: The lipid content increased during ripening at room temperature and a low temperature slowed down this increase. Linoleic acid content increased at low temperature, which was accompanied by an increase in the microsomal oleate desaturase (FAD2) activity and FAD2 expression. Furthermore, a low temperature attenuated lipid peroxidation as indicated by lower contents of malondialdehyde, hydroperoxide and total free fatty acid in T. grandis nuts during the ripening stage, as well as the down‐regulation of gene expression of lipid degradation‐related enzymes such as phospholipase D and lipoxygenases. CONCLUSION: The findings of the present study indicate that a low temperature increased polyunsaturated fatty acid contents by increasing FAD2 biosynthesis and decreasing lipid peroxidation, thereby improving the oil yield in T. grandis nuts during the post‐harvest ripening period. © 2019 Society of Chemical Industry